Assessing the effect of hypertension on the severity of coronary artery lesions in young female with acute coronary syndrome - Ruifang Liu; Fangxing Xu; Tongku Liu; Yujie Zhou; Xiaofan Wu (BMC Women's Health)
Abstract Background The fact that hypertension is associated with atherosclerotic cardiovascular disease in the elderly has been confirmed. However, very little is known about its impact on the severity of coronary artery lesions in young people, especially in young women. Objective To evaluate the effect of essential hypertension (EH) on the severity of coronary artery lesions in young women with acute coronary syndrome (ACS), and to provide a reference for clinical prevention and treatment. Methods From January 2003 to January 2022, 5220 young women (aged ≤ 44 years) who underwent coronary angiography (CAG) due to chest pain symptoms were retrospectively analyzed, of whom 2684 were diagnosed with ACS. After patients with diabetes, hypercholesterolemia, and smoking were excluded, 1772 patients were enrolled. According to whether the patient has EH or not, they were divided into EH combined with ACS group (EH-ASC group; n = 824) and non-hypertension ACS group (control group; n = 948). The severity of coronary artery lesions and the follow-up results after percutaneous coronary intervention (PCI) were compared between the groups. Results There was no significant difference in the type of ACS and the number of lesion vessels between the two groups (P > 0.05). The proportion of type B2 (17.11%) and type C (31.55%) lesions in the EH-ACS group was significantly higher than that (11.39% and 20.68%) in the control group (P < 0.05). The number of stents implanted (1.55 ± 0.95) and the length of stents (23.99 ± 6.77 mm) in the EH-ACS group were significantly greater than those (1.36 ± 0.75 and 22.34 ± 6.91 mm) the in control group (P < 0.05). During a follow-up period of 11–138 months, the cumulative rate of major adverse cardiac events (MACE) and target vessel revascularization (TVR) in the EH-ACS group (22.09% and 20.26%) was significantly higher than that (9.28% and 8.65%) in the control group (P < 0.05). Conclusion Hypertension exacerbates the severity of coronary artery lesions in young women with ACS. It is suggested that attention should be paid to the prevention and treatment of hypertension in young women, a special population, to reduce the prevalence of ACS, and a focus on improving hypertension awareness and management among young women could be beneficial in reducing the risk and severity of ACS.